1971
DOI: 10.1079/bjn19710061
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of lignin and quantitative aspects of ruminant digestion

Abstract: I. The technique for the quantitative estimation of lignin by digestion with 72 % H,S04 has been investigated. Two methods of pretreatment designed to eliminate interference products of carbohydrates and proteins were compared, namely (a) acid and pepsin and (6) acid detergent. The latter technique gave low lignin yields owing to the colloidal dispersion of lignin in the acid detergent treatment. Erroneous results arise from an inadequate digestion in 72 yo H,SO,. It was found preferable to filter the product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…33.5 + 3.76 kg) were surgically fitted with permanently-indwelling ruminal and abomasal cannulae as described by Komarek (1981) Ruminal OM digestion was corrected for the contribution of microbial OM to abomasal digesta; this was accomplished by estimating microbial N in abomasal digesta using a nucleic acid N: total microbial N ratio of 0.2, which Smith et al (1968) reported to be relatively constant (Smith 1975 (Faichney 1975). Previous research using automated total collection procedures supports the validity of this assumption (Porter and Singleton 1971), and Muntifering (1982) (Allden and Jennings 1962;Lamb and Eadie 1979). Limited energy supplementation may have no effect on forage intake, or may even stimulate forage intake (Lee et al 1987 For personal use only.…”
Section: Generalmentioning
confidence: 83%
“…33.5 + 3.76 kg) were surgically fitted with permanently-indwelling ruminal and abomasal cannulae as described by Komarek (1981) Ruminal OM digestion was corrected for the contribution of microbial OM to abomasal digesta; this was accomplished by estimating microbial N in abomasal digesta using a nucleic acid N: total microbial N ratio of 0.2, which Smith et al (1968) reported to be relatively constant (Smith 1975 (Faichney 1975). Previous research using automated total collection procedures supports the validity of this assumption (Porter and Singleton 1971), and Muntifering (1982) (Allden and Jennings 1962;Lamb and Eadie 1979). Limited energy supplementation may have no effect on forage intake, or may even stimulate forage intake (Lee et al 1987 For personal use only.…”
Section: Generalmentioning
confidence: 83%
“…For cattle, for example, the digestibility of forage was found to decline from around 80 to around 30% with increases in lignin contents from 2 to 10% (Jung and Vogel, 1986). Digestion of 10% of fodder lignin has been reported for ruminants (Porter and Singleton, 1971). Earthworms excrete lignin without appreciably degrading it (Crawford, 1981).…”
Section: The Significance Oflignin and Similar Compoundsmentioning
confidence: 96%
“…As already mentioned, the ADL method suffers from partial loss of lignin structure dissolved in the acid detergent solution (Porter and Singleton, 1971;Kondo et al, 1987;Lowry et al, 1994;Moore and Jung, 2001). However, we see no plausible explanation for the KL method results since KL is apparently insensitive to the loss of lignin observed with the ADL procedure, and both results are ash-free residues.…”
Section: Slopes Between Forage Degradability and Lignin Methodsmentioning
confidence: 41%
“…For legumes, the KL measurements were around 1.5 times over ADL values. Hatfield et al (1994) pointed out that the higher values for grass KL residues were not due only to protein contamination or incomplete hydrolysis of carbohydrates, but were more likely due to the solubilization of lignin components by the ADL treatment, as reported by several other authors (Porter and Singleton, 1971;Lowry et al, 1994;Shimojo and Goto, 1984;Jung et al, 1997;Moore and Jung, 2001). Jung et al (1999) used forage compositional analysis and bomb calorimetry to show that ADL concentrations could not account for sufficient gross energy, indicating that ADL might be an underestimate of lignin content.…”
Section: Lignin Concentrationsmentioning
confidence: 86%